Principles of coaxial illumination for photochemical reactions: Part 2. Model validation. Issue 2 (6th April 2020) - Meir, Glen; Leblebici, Mumin Enis; Kuhn, Simon; Van Gerven, Tom
Abstract: This study reports the principles and model equations for co‐ and counter‐current illumination, validated by experimental data. Current photochemical reactors which are homogeneously illuminated suffer from a light efficiency problem resulting in low light absorption and subsequent low productivity. Hence, the use of co‐ and counter‐current illuminated reactors, implementing larger path lengths, without altering the reactor's geometry, is of interest. In this article, we report a simple model to determine the conversion obtained by co‐ and counter‐current illumination techniques and compare against the current state‐of‐the‐art. Via experimental validation, we report the use of co‐ and counter‐current illumination to significantly boost the PSTY, a measure for photochemical reactor productivity, by a factor of 5 to 6 for same input concentration of reagent, solemnly by illuminating the reactor via co‐ and counter‐current (axially) instead of cross‐current (radially). Furthermore, we report that simply increasing the reagent concentration, thus absorbance, has a large influence on productivity, thus PSTY, of the reactor. By assessing the reactor's performance parameters, derived by modeling, which are the initial absorbance value ( A ) and the quantum photon balance ( ρϕ ), the reactor's operating point can be determined and adapted to operate in a more productive and efficient regime. Abstract :